The Role of Islamic Education in Addressing the LGBT Phenomenon Among Students in the Digital Era - Saniyyah Salwa Nabiilah; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
This research explores the contribution of Islamic education in responding to the LGBT phenomenon among university students in the digital age. The study is motivated by the increasing influence of digital technology and social media, which enable students to access a wide range of information and viewpoints related to gender identity and sexual orientation. Such developments create new challenges for students who are in the stage of developing their character, values, and personal identity. The objective of this research is to examine how Islamic education influences students’ perspectives, attitudes, and behaviors regarding the LGBT phenomenon based on Islamic teachings. This study adopts a qualitative library research approach by reviewing and analyzing relevant books, scholarly journals, and other academic references. The results reveal that Islamic education has a significant role in reinforcing religious beliefs, cultivating moral character, improving digital literacy skills, providing sexuality education grounded in Islamic principles, and supporting students through character-building and counseling programs. Consequently, Islamic education functions as an essential means of guiding students to address the LGBT phenomenon thoughtfully and critically within the context of an increasingly digitalized society.